Development of Worksheets to Reduce Misconception with a Conceptual Change Text Stretegy on Reaction Rate Factors - Muhammad Iqbal Al Fariki; Dian Novita (Universitas Lampung, 2021)
The purpose of this study is to determine the feasibility of the students’ worksheets that is developed to reduce misconceptions with the conceptual change text strategy on the material reaction rate factors. There are three aspects that review the feasibility of students’ worksheets, (1) Validity is to find out the validity of the developed students’ worksheets, (2) Practicality is to find out how practical the students’ worksheets which developed in learning process, (3) Effectiveness is to find out how effective students’ worksheets developed in reducing misconceptions. This research uses the Research and Development (RD) method which has 10 stages (1) Potentials and problems, (2) Data collection, (3) Product design, (4) Design validation, (5) Design revision, (6) Product testing, (7) product revision, (8) usage trial, (9) product revision, and (10) mass production. The subjects in this study are 12 students who detected misconceptions in the material reaction rate factors in class XII MIA 1, and MIA 2 SMA PLUS AR RAHMAT (High School) Bojonegoro. The results of this study indicate that the students’ worksheets developed are feasible to use to reduce misconceptions on the material reaction rate factors as evidenced by the acquisition of the results of the three aspects of feasibility as follow (1) Validity with the percentage of results 89.3% - 93.3% with Very valid category, (2) Practicality with a percentage of 90% - 93.75% with a very practical category, (3) Effectiveness with a percentage of 75% - 90.5% with an effective category.